Perbahasan epistemologi dalam wacana kalam al-Asha'irah: Analisis terhadap pemikiran al-Baqillani (m. 403H) dan al-Baghdadi (m. 429H) / Basri Husin - Basri , Husin (2018)
This study focuses on epistemological debates in theological Asharite's discourse with focus on al-Baqillani's (m. 403H.) and al-Baghdadi's (429H.) thought which is among the early Asharite's scholars after Imam Abu Hasan al-Asha'ari. In term of the development of Asharite's epistemological theological, al-Baqillani and al-Baghdadi play an important role by founding the basics and methods of epistemological thinking in the early stages. They are among the Asharite's scholars who started discussing the book with introduction of knowledge (epistemology) methods. Some of the key concepts they have presented are the definition and the nature of knowledge, the kinds of knowledge, the sources of knowledge, 'ilm and ma'rifah, the kinds of information and sophist to be an important guide to the later Asharite's scholar in term to build a comprehensive concept in the Asharite's epistemology of kalam. This study based on two methodologies which is data collection and data analysis consisting method of inductive, deductive and historical. The findings show that the theory of knowledge proposed by al-Baqillani and al-Baghdadi greatly influenced the later Asharite scholars to build a great holistic framework of knowledge. Furthermore, the analysis of this study show that the epistemological approaches by them are still relevant to defend 'Aqidah Islam. This is because the challenges of knowledge that arise from the past to the present are the same in terms of thier methodology or their thought whether the challenges come from both internal and external.